Investigations of HAWT airfoil shape characteristics and 3D rotational augmentation sensitivity toward the aerodynamic performance improvement - Kim, You Jin; Bangga, Galih; Delgado, Antonio (Sustainability, 2020)
This study investigates the impacts of different airfoil shapes on the 3D augmentation and power production of horizontal axis wind turbines (HAWTs). The aerodynamic effect from changing the leading and trailing edge of the airfoil is the emphasis of the research. Varied power produced from modifying sensitivity on 3D augmentations, caused by revamping airfoil shapes, are shown. The 3D correction law, considering the chord to radius ratio and the blades' pitch angle in the rotation, is applied to the airfoil lift coefficients. The blade element method (BEM) embedded in the software Qblade with modified lift coefficients simulates the power productions of three wind turbines from these airfoils. The comparisons of the boundary layer characteristics, sectional forces, and inflow angle of the blade sections are calculated. The k-omega SST turbulence model in OpenFoam visualizes the stall and separation of the blades' 2D section. The airfoils with a rounded leading edge show a reduced stall and separated flow region. The power production is 2.3 times higher for the airfoil constructed with a more rounded leading edge S809r and two times higher for the airfoil S809gx of the symmetric structure.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Aerodynamics; Airfoil; Boundary layer; HAWT; Rotational augmentation